Application of selection index for rice mutant screening under a drought stress condition imposed at reproductive growth phase - MAMIK SARWENDAH; ISKANDAR LUBIS; AHMAD JUNAEDI; BAMBANG SAPTA PURWOKO; DIDY SOPANDIE; AZRI KUSUMA DEWI (Society for Indonesian Biodiversity, 2022)
Abstract. Sarwendah M, Lubis I, Junaedi A, Purwoko BS, Sopandie D, Dewi AK. 2022. Application of selection index for rice mutant screening under a drought stress condition imposed at reproductive growth phase. Biodiversitas 23: 5446-5452. Drought is a condition of limited availability of water that can reduce rice growth and productivity, and may threaten food security. Therefore, efforts are needed to produce drought-tolerant rice genotypes. This study aimed to select drought tolerant of the M3 mutant upland rice population at the reproductive growth phase. This research was carried out in dryland at BATAN, Indonesia, from September 2020 to February 2021, using an augmented design. The study employed 360 ??genotypes of mutant upland rice and 5 check varieties, namely Salumpikit, IR20, IR64, Limboto, and Situgintung. The selection index was constructed based on multivariate analyses such as correlation, path, and Principal Component Analysis (PCA). The coefficient of the selected main component can be used as a selection index. Before selecting the character values of each genotype, the values were standardized to obtain the same degree of value. The results showed that grain weight per hill (W.G.), panicle density (P.D.), panicle length (P.L.), and the number of filled grains per panicle (NFG) could be used as selection criteria for mutant upland rice tolerant to drought at reproductive growth phase. The selection index formula was I = (5*0.44*WG) + (2*0.41*PD) + (0.23*PL) + (0.42*NFG). Selection of genotypes of mutant upland rice based on weighted index selection resulted in 89 genotypes with high yields and good agronomic characteristics so that they could be tested in further research.